Comparative Study of T Beam Bridge with Conventional Method and Finite Element Analysis - Yadav, Raghabendra; Sah, Binay Kumar; Yadav, Indra Narayan; Gupta, Dinesh Kumar (Journal of the Institute of Engineering, 2019)
The most commonly and popular type of bridge used in Nepal is T beam bridge due to it’s simple in design, construction and maintenance than other types. T-beam Bridge comprises of a concrete slab integral with girders. This type of bridges is more preferred when it comes to connectivity to short distances. So, it is necessary to update the analysis and design methods. Here, in this paper, there is an attempt to study the comparison of maximum bending moment due to live load in a girder and slab bridge for varying span length as 15m, 20m and 25m respectively of T Beam bridge using conventional method. The same bridge is analyzed as a three-dimensional model in finite element software as SAP2000, apply the same loading done for conventional methods and compared the results. The maximum bending moment results obtained from finite element model are lesser than Courbon’s method which looks more conservative.